Mechanics of Soccer Heading and Protective Headgear - Hassan, Mohd Hasnun Arif.; Taha, Zahari; Hasanuddin, Iskandar; Mohamed Mokhtarudin, Mohd Jamil; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This short book provides a concise study of the mechanics of head impact in a soccer heading manoeuvre. It describes the development and validation of finite element models of soccer ball and human head, as well as the simulation of brain dynamics after ball-to-head impact. In addition, it also presents a computational study of the efficacy of wearing protective headgear in mitigating the risk of concussion due to heading in soccer.
Concussion in Soccer -- Mathematical Modelling of Soccer Heading -- Soccer Ball Finite Element Model -- Human Head Finite Element Model -- Simulation of Soccer Heading Manoeuvre -- Analysis of Protective Headgear.
Keywords: Mechanics, Applied; Solids; Biomechanics; Biomedical engineering; Solid Mechanics; Biomechanics; Biomedical Engineering and Bioengineering